Impoliteness in the issue of bullying in the Wonder movie (2017) - Azizah, Nur; Fi’aunillah, Tristy Kartika; Swasono, Endratno Pilih (Journal of Research on English and Language Learning (J-REaLL), 2024)
This research aims to analyze the types of impoliteness strategy used by one of the characters (Julian) toward his interlocutor (Auggie) as the main character in Wonder movie (2017) based on Culpeper’s impoliteness strategy and how the issue of bullying portrayed in the movie. Julian’s utterances towards Auggie were taken as the data, described using descriptive qualitative method, and it was found that the dominant utterance used was negative impoliteness. Julian directly expresses his impoliteness through negative speech, threatening Auggie’s face rather than holding back. Finally, these findings concluded that impoliteness used gradually over time in aggressive or negative utterances represents verbal bullying behavior. The impoliteness strategy here is used to intimidate other people’s feelings and harm them mentally by insulting appearance, belittling the interlocutor, and threatening the interlocutor’s knowledge and abilities. Verbal bullying is directly related to using force to gain the bully’s advantage over a situation or environment. Bullies use intimidation to show social power and outright disrespect. On the other hand, the low self-control of perpetrators is the basis for jealousy of competition, and impoliteness in interactions then causes verbal bullying.